Genetic Profile of Human Papilloma Virus Circulating in Cervical Precancerous-Lesions of Cameroonian Women (Global Journal of Medical Research, 2023)
Background Cervical cancer is the most common cancer after breast cancer worldwide especially in developing countries Infection by Human Papillomaviruses HPV In Cameroon there is a paucity of studies focused on its epidemiology This study aimed at appraising the diversity of HPV genotypes circulating in precancerous cervical lesions observed in Cameroonian women For this study a total of 4063 women fulfilled inclusion criteria and they were enrolled For this sample only 1947 women presented precancerous cervical lesions This cross sectional study carried out in three areas of the Cameroon namely Niete Mokolo and Yaounde Methods Cervical swabs were obtained from each participant and thereafter undergone cytological analysis relied on Pap test techniques DNA was extracted from positive smears for genotyping of Human papilloma virus using multiplex PCR polymerase chain reaction method Data analysis was done by GraphPad Prism 5 and XLSTAT
Keywords: human papilloma virus; molecular epidemiology; precancerous lesions; cervical cancer; cameroon